Biological activity of entomopatogenic fungi on Premnotrypes vorax Hustache (coleoptera: curculionidae) - Villamil C., Jorge Enrique; Martínez O., John Wilson; Pinzón, Elberth Hernando (Revista de Ciencias Agrícolas, 2016)
Andean potato weevil Premnotrypes vorax Hustache causes economic losses in potato crop which could rise until 100% depending upon population level and crop management. The aim of this work was to determine the individual and combined pathogenic effect of two isolates of native Beauveria spp. Compared to commercial products (Beauveria spp. and Metarhizium anisopliae) for controlling P. vorax under field conditions. A completed randomized design, eight treatments, and four replicates was used. The inoculation was directed to the stem base, using a 5x108 conidia.g-1. Damage percentage, control percentage and yield at harvest time (t.ha-1) were evaluated. Results indicated that commercial products combination, Metaril® W.P + B. brongniartii ® W.P and Beauveria sp. Bv01 native isolate showed the lowest damage (3.1±0.06 and 3.5±0.2%, respectively), the highest control levels (77±0.46 and 76.7±1.78%, respectively), and the highest yield per ha (19±0.40t ha-1 and 18±0.25t ha-1, respectively). These results were significantly different (Duncan P≤0.05) to the other treatments. Treatment T6 was outstanding because it’s highest biological potential. This treatment represent a promissory alternative for controlling P. vorax.